2017
DOI: 10.1111/ajt.14260
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Pediatric Kidney Transplantation in Recipients of a Previous Non-Renal Solid Organ Transplant

Abstract: Children who receive a non-renal solid organ transplant may develop secondary renal failure requiring kidney transplantation. We investigated outcomes of 165 pediatric kidney transplant recipients who previously received a heart, lung, or liver transplant using data from 1988 to 2012 reported to the United Network for Organ Sharing. Patient and allograft survival were compared with 330 matched primary kidney transplant (PKT) recipients. Kidney transplantation after solid organ transplant (KASOT) recipients exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The adult population has been using RT following NRSOT for some time, with the pediatric population more recently starting to report successful cases of tandem transplants . Evidence thus far has demonstrated good outcomes—Hamdani et al demonstrated good graft survival data in patients receiving RT following SOT compared to primary RT. Despite increased mortality in patients requiring tandem transplants, graft survival was not statistically significant between primary RT recipients and those who received RT after SOT.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The adult population has been using RT following NRSOT for some time, with the pediatric population more recently starting to report successful cases of tandem transplants . Evidence thus far has demonstrated good outcomes—Hamdani et al demonstrated good graft survival data in patients receiving RT following SOT compared to primary RT. Despite increased mortality in patients requiring tandem transplants, graft survival was not statistically significant between primary RT recipients and those who received RT after SOT.…”
Section: Discussionmentioning
confidence: 99%
“…Overall patient survival was slightly worse in patients who had received prior SOT: 88% survival at 5 years and 75% at 10 years, compared to 97% at 5 and 10 years, respectively, for primary RT. This is theorized to be due to increased morbidity and mortality of receiving a prior SOT …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations